Efficacy of Sodium–Glucose Cotransporter 2 Inhibitors in Chronic Heart Failure: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Eskandar, Kirolos (Ukrainian Journal of Cardiovascular Surgery, 2025)
Background. Sodium–glucose cotransporter 2 (SGLT2) inhibitors are now a foundational therapy for heart failure (HF), yet uncertainties remain regarding their impact on mortality, recurrent events, patient-reported outcomes, and biomarkers. Aim. To evaluate the efficacy and safety of sodium–glucose cotransporter 2 (SGLT2) inhibitors in patients with chronic heart failure across the spectrum of ejection fraction, based on evidence from randomized controlled trials. Materials and Methods. We conducted a systematic review and meta-analysis in accordance with PRISMA 2020 (PROSPERO: CRD420251138644). PubMed, Embase, Cochrane CENTRAL, and ClinicalTrials.gov were searched through 25 June 2025. Eligible studies were randomized controlled trials (RCTs) of SGLT2 inhibitors versus placebo in adults with chronic HF. The primary endpoint was time to first cardiovascular (CV) death or HF hospitalization. Secondary outcomes included all-cause mortality, recurrent hospitalizations, quality of life, natriuretic peptides, and safety. Hazard ratios (HRs) were pooled using Hartung–Knapp random-effects models where definitions were consistent; other outcomes were narratively synthesized. Risk of bias was assessed with RoB 2, and the certainty of evidence with GRADE. Results. Five RCTs (n = 16,222) were included: DAPA-HF, EMPEROR-Reduced, DELIVER, SOLOIST-WHF (providing recurrent-event analyses), and DEFINE-HF (mechanistic, biomarker-focused). SGLT2 inhibitors reduced the risk of CV death or HF hospitalization (pooled HR 0.79, 95% CI 0.74–0.83; I² = 0%). The reduction in hospitalization was consistent across trials (HRs ≈ 0.69–0.75), while all-cause mortality showed a modest but significant benefit (HR 0.90, 95% CI 0.83–0.98). Trials consistently demonstrated improvements in Kansas City Cardiomyopathy Questionnaire (KCCQ) scores and natriuretic peptide response rates. Safety findings were consistent with the established SGLT2 inhibitor profile, with no signals of serious adverse events. Conclusions. SGLT2 inhibitors confer robust reductions in HF hospitalizations and provide supportive benefits on mortality, quality of life, and biomarkers across EF phenotypes, reinforcing their role as a cornerstone therapy in chronic HF.